Workload Analysis as a Basis for Human Resource Management at UD. Kreasi Lutvi - Simarmata, Fitri; Panjaitan, Friska Lamria; Catherine Genesia M, Felicia; Rahmadzar Saragih, Doni; Delvi Yanti, Eli (Accounting and Business Journal, 2025)
This study aims to analyze workload as the basis for human resource (HR) management at UD. Kreasi Lutvi using a descriptive qualitative approach based on literature studies. Data were obtained from secondary sources such as indexed scientific journals, research articles, and relevant publications in the field of HR management and workload analysis. Data collection techniques were carried out through systematic searches in online databases such as Google Scholar and ResearchGate using related keywords. The results of the study indicate that in an effort to optimally manage HR, UD. Kreasi Lutvi needs to pay attention to several important aspects, namely: (1) Imbalance of Workload in Production Units; (2) Lack of HR and Training Needs; (3) Classification of Workload Levels; (4) Impact of Excessive Workload on Health and Performance; (5) Planning the Number of HR Appropriately, and (6) Improving HR Management. This study is expected to be the basis for making strategic decisions related to HR management more effectively and efficiently.